2019
DOI: 10.1519/jsc.0000000000001944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Functional Movement Screen and a Novel Basketball Mobility Test as an Injury Prediction Tool for Collegiate Basketball Players

Abstract: Identifying injury risk and implementing preventive measures can assist in reducing injury occurrence and may ultimately improve athletic performance. Improper movement patterns often contribute to musculoskeletal (MSK) injuries. The validity of the Functional Movement Screen (FMS™) as an injury prediction tool for athletes remains unclear. We designed the Basketball-Specific Mobility Test (BMT) to represent the neuromuscular demands of basketball and identify deficiencies that may be indicative of greater MSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 19 publications
0
26
0
Order By: Relevance
“…Then, the methodological quality of the selected studies was assessed, choosing studies which had a score that was equal to or greater than 11 according to the STROBE statement. Thirteen studies exceeded the appraisal tool and no study was excluded 9 31–42. The study scores are found in table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the methodological quality of the selected studies was assessed, choosing studies which had a score that was equal to or greater than 11 according to the STROBE statement. Thirteen studies exceeded the appraisal tool and no study was excluded 9 31–42. The study scores are found in table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 12 studies were included in the meta-analysis according to the criteria explained above 9 31–41. The study selection process is shown in a flow chart in figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six research articles assessed the relationship between the FMS (or a portion of the test) between the FMS and another assessment tool. 43 , 44 , 63 , 73 , 105 107 Teyhen et al 63 evaluated the relationship between the FMS and the YBT in active duty service members finding that a better performance on the FMS was associated with a greater anterior reach on the YBT. Bond et al 44 and Paszkewicz et al 107 compared the FMS to a mobility test.…”
Section: Measurement Properties For Instrumentsmentioning
confidence: 99%
“… 43 , 44 , 63 , 73 , 105 107 Teyhen et al 63 evaluated the relationship between the FMS and the YBT in active duty service members finding that a better performance on the FMS was associated with a greater anterior reach on the YBT. Bond et al 44 and Paszkewicz et al 107 compared the FMS to a mobility test. Bond et al 44 suggested that while the newly constructed Basketball-Specific Mobility Test and the FMS may be appropriate for detecting musculoskeletal deficiencies, this screen and test do not accurately determine injury risk in basketball players at the collegiate setting.…”
Section: Measurement Properties For Instrumentsmentioning
confidence: 99%